Augmented Reality untuk Navigasi dan Pengenalan Fasilitas di Gedung Teknik Informatika Berbasis Android (Jurnal Sistem Informasi dan Ilmu Komputer, 2025)
This research aims to develop an Augmented Reality (AR) application as a navigation aid and facility introduction tool in the Informatics Engineering Building of Bengkalis State Polytechnic. This application is specifically designed to help new students and visitors understand and navigate the complex campus environment. By utilizing AR technology, the application provides an interactive guide that displays routes to various laboratories and presents detailed information about available facilities. The method used in developing this application is the Multimedia Development Life Cycle (MDLC), which consists of five stages: planning, design, development, testing, and launch. In the planning stage, a user needs analysis is conducted to ensure that the developed application meets the expectations and needs of end users. The design stage includes the creation of user interaction flows and visual interfaces, while the development stage involves the integration of AR technology with location data and campus facility information. Testing is conducted to ensure the functionality and accuracy of the navigation features and the quality of the user experience before the application is launched. The results of this study indicate that the AR application is able to provide a more interactive and informative experience than conventional media. New students and visitors can easily find laboratory locations and obtain a clear overview of campus facilities. In addition to improving navigation efficiency, this application also supports the adoption of digital technology in the campus environment. Thus, this research not only contributes in terms of ease of access to information, but also encourages the use of AR technology in the world of education, especially at Bengkalis State Polytechnic.